1936
DOI: 10.5962/bhl.title.6430
|View full text |Cite
|
Sign up to set email alerts
|

The adrenals, by Arthur Grollman.

Abstract: in man and in certain animals as composed in early life of three distinct physiological entities-the medulla, the cortex, and the androgenic tissue. The last named term has been coined to describe that portion of the adrenal which, in certain pathological conditions, gives rise to disorders of the reproductive system. This view of the tripartite nature of the adrenal is supported by many well-established facts. It affords a rational explanation of the relation of the adrenals to certain pathological conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1940
1940
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 103 publications
2
35
0
Order By: Relevance
“…THE acetylene method for determination of cardiac output seems to give very constant figures for a given individual under basal conditions, and the results obtained with Grollman's method seem also in most cases to agree well with the results obtained by methods based on Fick's principle [Grollman, 1932;Cooke & Priestley, 1937]. The use of the acetylene procedure in cases of heart failure in man, however, is based on the assumption that the solubility coefficient of acetylene in the blood of such cases is exactly known, and that the acetylene pressure found in the air of the rebreathing system agrees very accurately with the acetylene pressure of the arterial blood itself.…”
supporting
confidence: 76%
“…THE acetylene method for determination of cardiac output seems to give very constant figures for a given individual under basal conditions, and the results obtained with Grollman's method seem also in most cases to agree well with the results obtained by methods based on Fick's principle [Grollman, 1932;Cooke & Priestley, 1937]. The use of the acetylene procedure in cases of heart failure in man, however, is based on the assumption that the solubility coefficient of acetylene in the blood of such cases is exactly known, and that the acetylene pressure found in the air of the rebreathing system agrees very accurately with the acetylene pressure of the arterial blood itself.…”
supporting
confidence: 76%
“…The thyroid, although not essential for reproduction in animals, undoubtedly has some effect on reproductive function [Reiss & Pereny, 1928;Leonard, 1936;Zalesky & Wells, 1937;Benoit, 1937]. On the other hand, available evidence does not suggest that the adrenals and thyroid interact specifi¬ cally or intimately [Grollman, 1936]. Many observers have reported thyroid over-activity after adrenalectomy, and others [e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Threshold cycles in adrenalectomized rats In every mammalian species that has yet been tested complete removal of the adrenal glands leads to cessation of the oestrous cycle and death [see Grollman, 1936]. Bilateral adrenalectomy in the rat is occasionally not followed by death, presumably because of the existence of accessory adrenal tissue, and in such cases oestrous cycles continue.…”
Section: Methods Of Statistical Analysismentioning
confidence: 99%
“…Grollman and his collaborators 33 have reported that kidney extract given by mouth can effect a lowering of the blood pressure of hypertensive dogs and rats. Their rats were made hypertensive by reduction of the amount of renal substance.34 This claim has not yet been confirmed.…”
Section: The Treatment Of Experimental Renal Hypertension By Renal Ormentioning
confidence: 99%